Differential uptake of arginine derivatives by the human heteromeric amino acid transporter b0,+AT-rBAT (SLC7A9-SLC3A1) - Banjarnahor, Sofna; Scherpinski, Lorenz; Keller, Max; König, Jörg; Maas, Renke (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
L-arginine and its (patho-)physiologically active derivatives, L-homoarginine and asymmetric dimethylarginine (ADMA), show significant differences in their renal clearance. The underlying molecular mechanisms remain to be elucidated, but selective tubular transport protein-mediated mechanisms likely play a role. In the present study, we investigate the human heteromeric transporter b0,+AT-rBAT (encoded by the SLC7A9 and SLC3A1 genes) as a potential candidate because it is localized in the luminal membrane of human proximal tubule cells and capable of mediating the cellular uptake of amino acids, including L-arginine. Double-transfected Madin-Darby canine kidney (MDCK) cells stably expressing human b0,+AT-rBAT exhibited significant uptake of L-arginine and L-homoarginine, with apparent Km values of 512.6 and 197.0 μM, respectively. On the contrary, ADMA uptake was not saturated up to 4000 μM, with a transport rate > 5 nmol × mg protein−1 × min−1. With an IC50 value of 115.8 μM, L-arginine inhibited L-homoarginine uptake. Conversely, L-arginine only exhibited a partial inhibitory effect on ADMA uptake. Taken together, our data indicate that b0,+AT-rBAT may contribute to the differential renal handling of L-arginine, L-homoarginine, and ADMA.
CRIS-Team Scopus Importer:2025-02-04
Keywords: ADMA; b; L-arginine; L-homoarginine; Proximal tubule; SLC3A1; SLC7A9; Transport

Screening of commonly prescribed drugs for effects on the CAT1-mediated transport of l-arginine and arginine derivatives - Banjarnahor, Sofna; König, Jörg; Maas, Renke (Amino Acids, 2022)
The cationic amino acid transporter 1 (CAT1/SLC7A1) plays a key role in the cellular uptake or export of l-arginine and some of its derivatives. This study investigated the effect of 113 chemically diverse and commonly used drugs (at 20 and 200 µM) on the CAT1-mediated cellular uptake of l-arginine, l-homoarginine, and asymmetric dimethylarginine (ADMA). Twenty-three (20%) of the tested substances showed weak inhibitory or stimulatory effects, but only verapamil showed consistent inhibitory effects on CAT1-mediated transport of all tested substrates.
CRIS-Team Scopus Importer:2022-04-15
Keywords: ADMA; CAT1; Inhibition; l-Arginine; l-Homoarginine

Transport of L-Arginine Related Cardiovascular Risk Markers - Banjarnahor, Sofna; Rodionov, Roman N.; König, Jörg; Maas, Renke (Journal of Clinical Medicine, 2020)
L-arginine and its derivatives, asymmetric and symmetric dimethylarginine (ADMA and SDMA) and L-homoarginine, have emerged as cardiovascular biomarkers linked to cardiovascular outcomes and various metabolic and functional pathways such as NO-mediated endothelial function. Cellular uptake and efflux of L-arginine and its derivatives are facilitated by transport proteins. In this respect the cationic amino acid transporters CAT1 and CAT2 (SLC7A1 and SLC7A2) and the system y(+)L amino acid transporters (SLC7A6 and SLC7A7) have been most extensively investigated, so far, but the number of transporters shown to mediate the transport of L-arginine and its derivatives is constantly increasing. In the present review we assess the growing body of evidence regarding the function, expression, and clinical relevance of these transporters and their possible relation to cardiovascular diseases.
CRIS-Team WoS Importer:2021-01-15